Case report: Fast disease progression during adjuvant therapy with anti-PD-1 in stage III melanoma patients - Di Pietro, Francesca Romana; Verkhovskaia, Sofia; Falcone, Rosa; Poti, Giulia; Carbone, Maria Luigia; Morelli, Maria Francesca; Zappalà, Albina Rita; Morese, Roberto; Di Rocco, Zorika Christiana; Piesco, Gabriele; Chesi, Paolo; Failla, Cristina Maria; et al. (Frontiers in Oncology, 2024)
Background. Stage III surgically resected melanoma is a disease at high risk of recurrence. Immune checkpoint inhibitors (ICIs) and the target therapy with BRAF and MEK inhibitors significantly changed the outcome of patients with metastatic melanoma and several studies have also shown their benefit in the adjuvant setting for the delay of recurrence in stage III melanoma patients. Hyperprogression disease was observed as a possible adverse response to immunotherapy in the metastatic setting, suggesting that some patients could face addit ional risk of progression with ICIs, although no consensus was found for the correct definition of this event. Case presentation. We describe here two cases of rapid multiorgan metastatization during adjuvant immunotherapy in patients with stage III resected melanoma. Even though it would be not accurate to define this syndrome as hyperprogression because of apparent absence of the initial disease in the adjuvant setting, we observed in these two cases the same very rapid progression after first administration of adjuvant ICIs that resulted in death of patients within two months from the starting of treatment. Both patients had NRAS mutated melanoma.There is an urgent need for a better understanding of the causes of these fatal outcomes and for the identification of biomarkers that would allow to select the patients before offering them an adjuvant treatment, reducing the risk of hyperprogression. From these cases, we suggest that it could be useful a particular attention in proposing ICI adjuvant treatment based on the molecular profile.